(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: Hepatitis viruses are common cause of viral hepatitis, it has a varied distribution among people, it has more than five common types: Hepatitis A, B, C, D, E. Hepatitis B,C,&D occurred by parenteral route. Hepatitis E occurres specially in pregnant women by feco-oral route. Interleukin-4 (IL-4) protect human hepatocellular cell line from apoptosis and suppresses the expression and replication of hepatitis B virus. Exposure to HCV antigens increased L-10 production by polymorphonuclear cells and T cells. Aim of study: To monitor the significance of IL-4 and IL-10 among patients with chronic HBV and HCV, to find the frequency of confirmed hepatitis virus in Babylon City and to compare between their percentages and possible cause of transmission and method to prevent it Materials and Methods: A total number of 18 patients for each group of hepatitis B and C were taken to estimate of IL-4 and IL-10 which compared with 14 apparently healthy control group in Central Public Health Lab/ Babylon during the period from January-June, 2008. Results: The results showed highly significant decrease in IL-4 in both groups in comparison to control group while IL-10 showed highly significant increase in both group in comparison to control group. Conclusions: Immune factors are essential in the consequence of chronic HBV and HCV infection. Serum IL4 might be used as a laboratory parameter to indirectly assess liver damage instead of invasive histopathological examination. IL-10 might influence HCV and HBV infections susceptibility due to its anti-inflammatory action. IgG4 might further aggravate the disease course of HBV and HCV infection caused by IL-10.